THE EFFECTS OF SOCIAL SUPPORT TOWARD SOCIAL COMMERCE INTENTION IN INSTAGRAM: MEDIATING ROLE OF PERCEIVED USEFULNESS, TRUST AND SUBJECTIVE NORM - Albert, Adriel; Sihombing, Sabrina (Universitas Pelita Harapan, 2022)
Nowadays, s-commerce has quickly become an important component of business tools, driving more individuals to access s-commerce to create new businesses and conduct transactions. This s-commerce has evolved into e-commerce, where every transaction and business is developed by the rapid usage of the internet. This research is being conducted to find out and understand the effect of negative comments appearing on the Instagram platform. The goal of this research is to build on the technology acceptance model, theory of planned behavior, and theory of reasoned action to investigate the link of variables between social support and social commerce intention, which is mediated by perceived usefulness, trust, and subjective norm. In this study, social support variables are using a second order model, which is represented by informational support and emotional support. The independent variables in this study include social support, trust, subjective norms, and perceived usefulness. The researcher employed a quantitative method and a non-probability sampling method which is purposive sampling, and the data was obtained by distributing online questionnaires using google forms. There are 30 samples obtained for preliminary testing and 260 samples taken for the actual testing, with the requirements of having an Instagram account and ever purchasing a product promoted by Instagram. The preliminary study's data are subjected to reliability and validity testing. The reliability and validity of the data obtained for the actual test are examined. Next, the data is examined using Structural Equation Modeling (SEM) to evaluate each hypothesis and generate a conclusion. As a result, all eight hypotheses are supported. This study includes managerial implications, recommendations for future research, and theoretical implications.